Public service reform in Tanzania - LUVANDA, Vonyvaco (KDI School, 2016)
Along the implementation of public reform iniatives, Tanzania adopted Client Service Charter (CSC) as one of Performance Management System. The objective was to increase compliances to the citizen’s need by engaging them in delivering and management of public service. It is more than decade since the adoption and operationalization of the CSC. Hence this study came to assess the effectiveness implementation of CSC in public service. The study was conducted in all Ministries as well as in few Executive Agencies, Independent Departments and Regional Offices. The main research question in the study was to what extent CSC impacts service delivery in Tanzania public service. The study was undertaken based on three research questions that formed three objectives of this study. The first research question examines the efforts that have been undertaken by government to institutionalize the charter. The second research question analyses the factors and the extent have contributed to whether success or failure of the CSC implementation. The third research question aiming at looking challenges that affecting implementation of CSC. The study employed primary data, 33 public organizations were involved of which 32 are the main CSC implementers and one organization is the overall public service reform coordination office ‘President’s Office’. Interview for this study were undertaken in the 32 organizations (implementers), while the President’s Office provides researcher with broad information on CSC implementation in public service. Moreover, the researcher employed secondary data ̶ literatures relevant to the subject matter were involved include books, articles, journals, papers and research studies. Also, all available public service reform documents in Tanzania such monitoring reports, studies, progress performance reports were involved The researcher presented the finding of this study in descriptive and explanatory mode. In addition, researcher presented various remarkable case studies and best practices observed from CSC implementation, the case studies were highlighted to support findings obtained from the respondents as well as from the secondary data. The finding shows that CSC is operationalized to the most of public organizations. Similarly, most of the factors/ areas/ or variables that were established under this study have been implemented by the government with intention of ensuring CSC objective realized. Specifically, citizens’ awareness through established government communication strategies is receiving high attention. On other hand, CSC was institutionalized in most of public organizations. Other areas that support CSC achievement such as training, M&E, CHM, BPI, and ICT were also implemented. Further, the finding showed there is increase of citizens’ awareness, participation as well as compliances to the citizen needs due to CSC utilization. Therefore, based on finding of the study together with the identified case studies, researcher can conclude that adoption of CSC in public service have positively impact in improving public service delivery, in spite of challenges that still exist. The finding shows the areas that still needs attention including strengthening participation and communication in order to raise awareness to all citizens about their rights and hence demand better services from the Government. Also comprehensible enforcement and rewarding mechanism should be introduced to enhance accountability. ICT should be employed seriously in order to improve business process across the public service since re-engineering of business processes, computerize processes will reduce bureaucracy.
Thesis(Master) --KDI School:Master of Public Policy,2016